Metabolic reprogramming of three major nutrients in platinum-resistant ovarian cancer - Yan, Jinbowen; Xu, Fangzhi; Zhou, Dan; Zhang, Shuo; Zhang, Bo; Meng, Qingwei; Lv, Qiubo (Frontiers in Oncology, 2023)
Metabolic reprogramming is a phenomenon in which cancer cells alter their metabolic pathways to support their uncontrolled growth and survival. Platinum-based chemotherapy resistance is associated with changes in glucose metabolism, amino acid metabolism, fatty acid metabolism, and tricarboxylic acid cycle. These changes lead to the creation of metabolic intermediates that can provide precursors for the biosynthesis of cellular components and help maintain cellular energy homeostasis. This article reviews the research progress of the metabolic reprogramming mechanism of platinumbased chemotherapy resistance caused by three major nutrients in ovarian cancer.